Pareto-improving tax reforms and the Earned Income Tax Credit - Felix Bierbrauer; Pierre Boyer; Emanuel Hansen (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
This paper provides necessary and sufficient conditions for the existence of Pareto-improving tax reforms. The conditions can be expressed as sufficient statistics and have a wide range of potential applications in public finance. We discuss one such application in detail: the introduction of the Earned Income Tax Credit (EITC) in the US. We find that the EITC can be viewed as a response to an inefficiency in the tax and transfer system prevailing at the time. This adds a newperspective to the literature on why the EITC is a good idea, emphasizing Pareto improvements rather than equity-efficiency trade-offs.
Keywords: C72; D72; D82; H21; 330; Tax reforms; Non-linear income taxation; Optimal taxation; Earned Income Tax Credits; Pareto Efficiency